Estratégias utilizadas por adultos na aprendizagem de língua inglesa: ultrapassando barreiras linguísticas - Szezecinski, Antonio Filipe Maciel (2018)
Bilingualism is somehow linked to the matter of what makes a language reach a global language status. Thereby, it becomes essential nowadays on learning a foreign language, especially for the adult public, once they seek the foreign language study for professional reasons. Thus, the present thesis, which is inserted in the Research Line Education of Teachers, Theories and Educational Practices of the Post-Graduation Program in Education of La Salle University, aims to analyze how learning strategies are assigned and used by adult students during an English Language acquisition. For the effectuation of this study, the use of a quality nature research, through a case study as a way to comprehend such phenomenon. As for the data collection obtained through the research, two basic level groups had been taken as a main scene from a language school set in the city of Canoas, Rio Grande do Sul. Observation guides were used throughout the study. To achieve the results it had been used the Discursive Textual Analysis. The analysis had been divided in three important moments. The first one, named as the beginning categorization, where the gathered answers from the students’ interviews would be coinciding or not with each other. Thus, they had been shaped into beginning unities. From the formation of 23 beginning unities, a second moment for the analysis had occurred, labeled as the “intermediary categorization”. In this one, the early points again had been merged or drifted away from each other to form new unities, totalizing in this moment six intermediary unities. In the end, the analysis had reached its objective with a final categorization, following the same procedure from the early moments, thus forming two ending unities. As a result, it has been perceived that for adult students to achieve the essence of a second language acquisition, many factors need to be considered, from the students’ presented insecurities, related to their oral and written production, as well as of an ongoing use of Portuguese in moments of production to suppress the same apprehensions. For this reason, this ends up to become an obstacle to their learning and acquisition, since their communicative production in the language ends up to limit itself. Passing through small tasks to more complex ones, the English language acquisition and learning will only happen if they are supported by the communicative goals and when the student perceives him/herself as the main agent of his/her learning. In addition, the presence and support from the teacher in the course of their acquisition and learning process also reveals as an important factor for the development of the language. Through the incentive that the teacher provides to the use of the language, or even by exploring all the internal resources that the students have already possessed, the teacher works, alongside the students, as another instigating element for the practical use of the Language. Therefore, it has been perceived that the adult student’s learning does not only occur with the presence of a textbook, not even throughout the use of any additional material offered by the teacher. Learning is nothing but a set of initiatives taken by the student. Such initiatives that aim for a main objective, in this case an English Language acquisition, thus making it possible for the learning to happen.